Citogenômica e evolução cariotípica em primatas do novo mundo - Naiara Pereira de Araújo (2017)
The New World monkeys, or Platyrrhini, comprise a highly diversified group of mammals, with great morphological, behavioral, and ecological variation, which often make their identification difficult. Platyrrhini are also characterized by great chromosomal variation, often resulting from inversions, fusions/fissions, centromeric repositioning, and variation in heterochromatic content. Chromosome rearrangements are rare genomic events and can thus be used as markers for the reconstruction of evolutionary history. We used comparative chromosome banding and painting with human chromosome-specific (HSA) probes to identify the mechanisms involved in the karyotypic differentiating of Callicebus nigrifrons and Aotus infulatus. We detected four fusions (HSA 1b/1c, 3c/8b, 13/20, and 14/15/3/21) and one fission (HSA 2/22) as synapomorphies of Callicebus. The comparison of our results with those previously published for Callicebus, Cheracebus, and Plecturocebus allowed us to hypothesize an ancestral Callicebinae karyotype with 2n=48. The associations HSA 2/22, 7/15, 10/11, and the inversion of HSA 2/16 were present in all three genera and were thus likely present in the ancestral Callicebinae karyotype. The comparison of the data obtained in Aotus infulatus with those previously reported for this genus revealed seven shared derived associations (HSA 1/3, 1/16, 2/20, 4/15, 7/11, 10/11, and 16/22) and an inversion of HSA 14/15, resulting in HSA 14/15/14/15. The chromosome painting results allowed us to infer an ancestral Aotus karyotype with 2n=52 and to detect rearrangements associated with interspecific variations. We also investigated the structure, organization, and chromosomal distribution of satellite DNAs in Callitrichini. The analysis of the sequenced genome of Callithrix jacchus led to the identification of, in addition to the alpha satellite DNA, a satellite DNA that we named MarmoSAT, composed by 171-bp motifs and located in the subtelomeric and interstitial regions of Callithrix, Mico, and Callimico chromosomes. Besides its monomeric organization, MarmoSAT also presented higher-order repeats of 338-bp in Callimico. The transcription profile and the subtelomeric location of MarmoSAT allowed us to suggest that it may be involved with the regulation of telomerase and the modulation of the telomeric chromatin in these species.